Utility of a Computer-assisted Rod Bending System to Avoid Pull-out and Loosening of Percutaneous Pedicle Screws. Issue 3 (April 2021) - Ohba, Tetsuro; Ebata, Shigeto; Oda, Kotaro; Tanaka, Nobuki; Haro, Hirotaka
Abstract : Study Design: This was a retrospective observational study of a cohort of consecutive patients. Objective: To compare the influence of (1) manual and (2) computer-assisted (CA) rod bending techniques on pedicle screw pull-out resulting in loosening during rod reduction and final tightening. Summary of Background Data: Our recent study showed screw pull-out during rod reduction might be a risk factor for loosening of percutaneous pedicle screws (PPSs) postoperatively, resulting in worse postoperative back pain. We retrospectively analyzed data from 53 consecutive patients who underwent minimally invasive lumbar or thoracic spinal stabilization using intraoperative computed tomography image (CT)-guided navigation with conventional manual rod bending or CA rod bending and were followed up for 1 year. Method: Screw pull-out length was measured on axial CT images obtained immediately after screw insertion and postoperatively. Loosening of screws and clinical outcome were evaluated radiographically, clinically, and by CT 1 year after surgery. The frequencies of screw pull-out and screw loosening between the 2 rod bending techniques were compared. Lumbar pain-related factors for both groups of patients were determined preoperatively and 1 year after surgery. Results: Overall, 360 pedicle screws were placed in the manual group and 124 pedicle screws were placed in the CA group. There was no significant difference in the mean age, sex, bone mineral density, mean stabilized length, or smoking habits of patients between the groups. The diameters, lengths, and trajectory angle (axial and sagittal) of the screws placed were not significantly different between the groups. Screw pull-out rate/length and loosening in the CA group was significantly lower than that in the manual group. Postoperative low back pain improved significantly in the CA group compared with that in the manual group. Conclusion: CA bending is useful to avoid PPS pull-out during rod reduction and screw loosening postoperatively. CA bending is useful to avoid PPS pull-out during rod reduction and screw loosening postoperatively. This result might have been a factor leading to reduced postoperative back pain in the CA group, however, that future studies are need to investigate this association.